Transformation of the image of a woman of nomadic culture in Tuvan literature: the works by A. M. Lamazhaa - Samdan, Zoya B. (The New Research of Tuva, 2020)
The article examines the changes in the portrayal of a woman of nomadic culture in the works of Tuvan writer, a descendant of a shaman family, medical doctor A. M. Lamazhaa. We examine her collection of short stories and a novel ‘The Roads of the Silver Shamanesses’ (2011, 2019). The culture of Tuvan nomads has been changing during the entire 20th century, and there were inevitable losses along the way. This process was accompanied by changes in the traditional system of values and the role of women in Tuvan society. A. M. Lamazhaa is among the few Tuvan writers who focused on the rarely addressed issue of the shamans’ fate. The image of a woman of the Tuvan nomadic culture has for the first time been recreated in the genre of a novel. At the same time, the writer makes use of the folklore and neo-mythologist elements in her text. Both texts are written in the form of third-person objectified narration. But the author-narrator somewhat associates herself with the main character, which adds a degree of biographism to her work. There are four stages in the evolution of the image of a woman of nomadic culture: origin, formation, transformation, and affirmation. They correspond to the stages of evolution of a woman as a protector of nature: the guardian of traditional family values; the guardian of traditional kinship values; the modern woman as a keeper of the historical memory of generation and ethnicity.